Antibiotic-Induced Neutropenia in Pediatric Patients: New Insights From Pharmacoepidemiological Analyses and a Systematic Review - Battini, Vera; Mari, Alessandra; Gringeri, Michele; Casini, Francesca; Bergamaschi, Francesco; Mosini, Giulia; Guarnieri, Greta; Pozzi, Marco; Nobile, Maria; Zuccotti, Gianvincenzo; Clementi, Emilio; Radice, Sonia; et al. (Frontiers in Pharmacology, 2022)
ABSTRACT Aim: to characterize pediatric cases of antibiotic-associated neutropenia through a multidisciplinary approach, focusing on the temporal association between the wide spectrum of treatment options and the occurrence of this relatively uncommon but potentially clinically relevant adverse event. Methods: we carried out a pharmacoepidemiological analysis based on the FDA Adverse Event Reporting System (FAERS) database, a retrospective chart review and a systematic review of the literature, focusing on the time to onset (TTO) of this side effect, in the pediatric clinical setting. Results: A total of 281 antibiotic-related neutropenia events, involving 11 categories of antibiotics, were included in the TTO analysis. The median TTO ranged from 4 to 60 days after the start of the therapy. A shorter median TTO was found from the retrospective chart review [16 patients: median days (25th-75th percentiles) = 4(3-5)], compared to 15(9-18) vs 10(6-18) for literature (224 patients) and FAERS (41 cases), respectively. The ATC classes, J01X, J01F, J01E and J04A, and the median TTOs retrieved from more than one source revealed high accordance (p>0.05), with J01X causing neutropenia in less than a week and J01F/J01E/J04A in more than 10 days. Antibiotics were discontinued in nearly 34% of cases. In FAERS reports, half of the patients experiencing neutropenia were hospitalized. Conclusion: Whereas antibiotic associated neutropenia is benign in the majority of cases, yet it should not be neglected as, even if rarely, it may put children at higher risk of clinical consequences. Clinicians’ awareness of antibiotic-associated neutropenia and its mode of presentation contributes to the continuous process of monitoring safety of antibiotics.